2006
DOI: 10.4012/dmj.25.339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acetic NaF Solution on the Corrosion Behavior of Stainless Steel Orthodontic Brackets

Abstract: This study assessed the effect of acetic NaF solutions on stainless steel orthodontic brackets. Acetic acid was added to a 0.1% NaF solution to make two solutions, one with pH 3.5 and the other with pH 6. For the two different stainless steel brackets(Tomy, Dentaurum)used in this study, they had a similar elemental composition -except with Mo(molybdenum) in the Tomy bracket. The brackets were then immersed in the prepared test solutions for three days and their responses evaluated. In terms of hydrofluoric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…The MF-induced level of Fe elution from the SUS wires in the solutions containing 450 and 900 ppm of fluoride was similar to the level of Fe elution in the MF-induced AS group. The level of Ti elution from the Ni-Ti wires in the solutions containing 450 and 900 ppm of fluoride effectively supported the results of previous reports [2][3][4][5][6] . The pH of AS with MF exposure was lower than those of the fluoride-containing solution with/ without MF exposure; however, these pH values were much higher than the depassivation pH of SUS and Ni-Ti wires, so the pH could not be the cause of this metallic elution.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The MF-induced level of Fe elution from the SUS wires in the solutions containing 450 and 900 ppm of fluoride was similar to the level of Fe elution in the MF-induced AS group. The level of Ti elution from the Ni-Ti wires in the solutions containing 450 and 900 ppm of fluoride effectively supported the results of previous reports [2][3][4][5][6] . The pH of AS with MF exposure was lower than those of the fluoride-containing solution with/ without MF exposure; however, these pH values were much higher than the depassivation pH of SUS and Ni-Ti wires, so the pH could not be the cause of this metallic elution.…”
Section: Discussionsupporting
confidence: 90%
“…Fluoride-containing mouthwashes and toothpastes for home use, and fluoride treatments in the dental clinic, are effective methods for preventing dental caries in dental patients with fixed appliances, especially those with complicated morphologies 1) . However, fluoridecontaining environments also reduce the corrosion resistance of pure titanium and titanium alloys through the breakage of their protective surface oxide layers [2][3][4] , and corrode stainless steel dental appliances 5,6) . The corrosion resistance of titanium depends on the fluoride concentration and the pH value 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, stainless steel wire was found to show low reactivity, low discoloration, and low dissolution in fluoride-containing solutions 27,28) . This suggests that chromium oxide has good resistance to fluoride-induced corrosion, and that corrosion resistance to fluoride differs between titanium oxide and chromium oxide, with corrosion occurring in titanium oxide, but being resisted in chromium oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Chromium oxide films on cobalt-chromium alloys and stainless steel on dental alloys show consistently good corrosion resistance in an oral environment [26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SS brackets are composed mainly of Fe, Cr, and Ni. Gwinnett (1982) and Jang et al (2006) showed that Fe, Cr, and Ni ions are released from SS during the corrosion process. Schiff et al (2006) showed that corrosion includes two consequences: the risk of local allergic reactions caused by Ni ions released and the deterioration in the mechanical performance of the archwire to bracket system, which would adversely affect the final aesthetic result.…”
Section: Discussionmentioning
confidence: 99%